Enhancing Safety in Military Aviation: A Systematic Approach to the Development of AI Certification Standards - Raquel Delgado-Aguilera Jurado; Vicent Ortolá Plaza; Xiaojie Ye; María Zamarreño Suárez; Francisco Pérez Moreno; César Gómez Arnaldo (Engineering Proceedings, 2025)
This article proposes a systematic methodology for developing a certification standard for AI safety-critical systems in military aviation, combining military and civil airworthiness references. It involves a thorough analysis conducted to identify overlaps, contradictions, and specific needs for AI certification in this field. The methodology includes incremental updates to a foundational certification framework, continuously integrating new references. An illustrative application to an ISO reference demonstrates the process of extracting AI certification requirements, and systematically derived requirements from various ISO references exemplify the methodology’s efficacy. The aim of this approach is to consolidate pertinent information to establish robust certification standards, ensuring comprehensive coverage of relevant criteria.